2017
DOI: 10.1161/jaha.117.006397
|View full text |Cite
|
Sign up to set email alerts
|

Newly Identified NO‐Sensor Guanylyl Cyclase/Connexin 43 Association Is Involved in Cardiac Electrical Function

Abstract: BackgroundGuanylyl cyclase, a heme‐containing α1β1 heterodimer (GC1), produces cGMP in response to Nitric oxide (NO) stimulation. The NO‐GC1‐cGMP pathway negatively regulates cardiomyocyte contractility and protects against cardiac hypertrophy–related remodeling. We recently reported that the β1 subunit of GC1 is detected at the intercalated disc with connexin 43 (Cx43). Cx43 forms gap junctions (GJs) at the intercalated disc that are responsible for electrical propagation. We sought to determine whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Interestingly, the recent inclusion of aldosterone antagonist eplerenone in early DMD cardiomyopathy treatments delayed progressive cardiac dysfunction when compared with standard therapy (89). Eplerenone's direct impact on Cx43 is unknown, but evidence suggests that it may enhance phosphorylation and improve Cx43 function through the nitric oxide (NO) pathway (90), a key mediator of Cx43 localization in hypertrophic hearts (91).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the recent inclusion of aldosterone antagonist eplerenone in early DMD cardiomyopathy treatments delayed progressive cardiac dysfunction when compared with standard therapy (89). Eplerenone's direct impact on Cx43 is unknown, but evidence suggests that it may enhance phosphorylation and improve Cx43 function through the nitric oxide (NO) pathway (90), a key mediator of Cx43 localization in hypertrophic hearts (91).…”
Section: Discussionmentioning
confidence: 99%
“…Rat mesangial cells treated with the NO donor S-nitroso-N-acetylpenicillamine (SNAP) or 8-Br-cGMP increased expression of Cx43 [ 101 ]. Additionally, GC1 −/− mice exhibit Cx43 phosphorylation in the intercalated disc of cardiac tissue, resulting in dysfunctional gap junction electrical conductivity [ 102 ]. Finally, in rodent vascular smooth muscular cells, Cx43 expression increases in response to either 8-Br-cGMP treatment or BAY 41-2272, a GC1 stimulator, and PKG inhibition reverses this increase [ 103 ].…”
Section: No-cgmp Signaling In Glial Cellsmentioning
confidence: 99%
“…Potent drugs are now available to augment these signaling systems with conventional soluble guanylate cyclase (sGC) stimulators, novel NO-independent sGC stimulators, GC-A and GC-B agonists, and PDE inhibitors [ 182 , 184 , 185 , 186 ]. Guanylate cyclase has recently become a new target for the treatment of heart failure [ 187 , 188 ]. In clinical trials, the incidence of death from heart failure has been reported to be lower for patients receiving vericiguat, a guanylate cyclase stimulator [ 188 ].…”
Section: Myofilaments and Ca 2+ Responsivenessmentioning
confidence: 99%